Cell-to-Cell Signaling Networks at the Blood-Brain Barrier in Health and Disease - Joseph H. McCarty (Arteriosclerosis, Thrombosis, and Vascular Biology, 2026)
The blood-brain barrier (BBB) is a highly specialized interface between the central nervous system and the peripheral circulation, crucial for maintaining neuronal homeostasis and protecting the brain parenchyma from potentially harmful blood-borne substances. This review examines the molecular and cellular organization of the BBB and explores how defective cell adhesion and signaling networks lead to BBB pathologies. I discuss the intricate architecture of brain endothelial cells within the context of the larger multicellular neurovascular unit, highlighting the roles of pericytes, astrocytes, as well as ECM (extracellular matrix) proteins and growth factors in vascular basement membranes. Recent advances in understanding endothelial cell tight junction dynamics, transport mechanisms, and communication pathways within the neurovascular unit are presented, with a particular emphasis on astrocyte-endothelial communication. Furthermore, I detail how abnormal astrocyte-endothelial signaling leads to BBB breakdown and contributes to various neurological disorders. In summary, this review synthesizes current knowledge of BBB biology, with particular emphasis on recent discoveries in signaling pathways, intercellular adhesion, and dynamic regulatory mechanisms that govern barrier function. By integrating findings from functional studies across multiple models, this review provides critical insights into both fundamental BBB biology and the potential development of translational approaches for treating human cerebrovascular disorders. Understanding these complex mechanisms not only advances our knowledge of normal brain homeostasis but also illuminates promising therapeutic targets and strategies for addressing conditions ranging from stroke to neurodegenerative diseases, ultimately paving the way for more effective clinical interventions that can preserve or restore BBB integrity.